2016
DOI: 10.1177/0972150916631214
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Employer Branding and Employee Retention

Abstract: The employment environment, nowadays, is becoming increasingly competitive. In such competitive environment, employer branding is fast emerging as a long-term human resource (HR) strategy to attract and retain talented workforce. The purpose of this article is to determine the antecedents of employer branding from the perspective of current employees. Most studies are dedicated to the examination of employer branding as a talent attraction technique among potential employees. However, the present research exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
102
0
25

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 57 publications
11
102
0
25
Order By: Relevance
“…Therefore, organizations are duty bound to recruit and retain the most valuable, resourceful, efficient and productive workforce for optimal benefits. This is because turnover has a negative impact on organization especially on productivity, service and profitability (Tanwar, & Prasad, 2016), In fact, the cost of replacing and hiring new employees is high and finding skilled employees can also be difficult (Kwenin, Muathe, & Nzulwa, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, organizations are duty bound to recruit and retain the most valuable, resourceful, efficient and productive workforce for optimal benefits. This is because turnover has a negative impact on organization especially on productivity, service and profitability (Tanwar, & Prasad, 2016), In fact, the cost of replacing and hiring new employees is high and finding skilled employees can also be difficult (Kwenin, Muathe, & Nzulwa, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sumber daya manusia yang dibutuhkan perusahaan harus memiliki komitmen organisasi terbaik yang didapatkan berdasarkan proses panjang yang dilakukan perusahaan (Tanwar & Prasad, 2016). Prosesnya merupakan pencarian ketat maupun pelatihan yang diberikan perusahaan itu sendiri.…”
unclassified
“…Prospective applicants at job fairs reportedly gain a sense of the 'personality' of an organization and are thus able to assess their potential fit with the organization [22]. Related to the point of attrition, researchers [13] also found that the outcomes of employer branding, such as job satisfaction and psychological contract, influence subsequent employee retention. In their qualitative study of an IT company, a positive relationship between employer branding and commitment also support brand advocacy by employees [13].…”
Section: Employer Branding and Recruitment At Virtual Fairsmentioning
confidence: 99%
“…Related to the point of attrition, researchers [13] also found that the outcomes of employer branding, such as job satisfaction and psychological contract, influence subsequent employee retention. In their qualitative study of an IT company, a positive relationship between employer branding and commitment also support brand advocacy by employees [13]. Such advocacy may complement employer branding and recruitment at virtual fairs.…”
Section: Employer Branding and Recruitment At Virtual Fairsmentioning
confidence: 99%
See 1 more Smart Citation